1997
DOI: 10.1103/physreva.56.3726
|View full text |Cite
|
Sign up to set email alerts
|

Electron-impact-excitation cross sections of lithiumlike ions

Abstract: We present an easy to use expression for cross sections of electron-impact-induced 1s 2 nl→1s 2 nЈlЈ excitation transitions with 2рnрnЈр4 in multiply charged ions of lithium isoelectronic sequence. This expression is based on our computations by convergent close-coupling ͑CCC͒ and Coulomb-Born with exchange and normalization ͑CBE͒ methods. We show scaling of the CCC and CBE cross sections with atomic number Z and use this scaling for presentation of the cross-section data. For 6рZр30 the scaling is accurate to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 24 publications
(3 reference statements)
1
14
0
Order By: Relevance
“…␤ 21 is given by (Obtained similarly by from the detailed balance relation applied to the impact-excitation cross section given in Ref. 26…”
Section: ͑12͒mentioning
confidence: 99%
“…␤ 21 is given by (Obtained similarly by from the detailed balance relation applied to the impact-excitation cross section given in Ref. 26…”
Section: ͑12͒mentioning
confidence: 99%
“…Such comparisons were done, e.g., for the R-matrix with pseudostates and K-matrix method results [15,16,17]. For higher-Z ions (Z ≥ 4), a detailed comparison of all excitation cross sections between the states with the principal quantum number n ≤ 4 has shown that the CCC data practically coincide with the perturbative Coulomb-Born-exchange calculations [18]. Furthermore, a recent paper on electron-impact excitation in Be II and B III (also including the transitions between the excited states up to n ≤ 4) again demonstrated a high level of agreement between the CCC and the K-matrix cross sections [17].…”
Section: Theorymentioning
confidence: 99%
“…Our main source of excitation data is the Coulomb-Born-exchange unitarized code ATOM [15] which combines a high calculational speed with a good accuracy, especially for moderately-and highly-ionized atoms. Previously we have shown that ATOM excitation data for H-and Li-like ions very well agree with the cross sections calculated by the more sophisticated convergent close-coupling (CCC) method [17,18]. Nevertheless, a use of more precise data is made whenever possible; for example, our database of collisional cross sections for neutral Helium was developed using the latest recommended CCC fits [19].…”
Section: Collisional-radiative Modelmentioning
confidence: 99%